The effect of using game-based learning (bamboozle) on the learning motivation of fourth grade students at Madrasah Ibtidaiyah Payungan, Kaliwungu District, Semarang Regency - Erni Tri Rahayu; Lailla Hidayatul Amin; Herri Gunawan; Abdu Robbi Rasul Nuh Al Hawary (At Turots: Jurnal Pendidikan Islam, 2024)
The transformation of education in Indonesia requires the world of education to be able to adapt to changing times, which is the widespread use of various kinds of digital technology in the world of education. Digital technology has become an important part of today's learning methods. The lack of teacher understanding of the use of renewable learning media methods and media causes low student motivation. The purpose of this study is the first to describe how the use of Game-Based Learning (Baamboozle) in the IPAS subject of grade IV students of Madrasah Ibtidaiyah Payungan in the 2024/2025 academic year, the second to describe how high is the learning motivation of grade IV students of Madrasah Ibtidaiyah Payungan in the IPAS subject, the third to describe how big is influence of the use of Game-Based Learning (Baamboozle) on the students’ learning motivation of IV grade students of Madrasah Ibtidaiyah Payungan in the IPAS subject in the 2024/2025 academic year. This research method uses a quantitative approach. The population in this study was the IV grade students of Madrasah Ibtidaiyah Payungan, Kaliwungu Semarang with a total of 39 students. The research was conducted at Madrasah Ibtidaiyah Payungan with sampling using comlete sampling totaling 39 students. While the data collection is done through observation, questionnaires and documentation where the instrument of the questionnaire has been validated and reliable. Furthermore, it was analyzed by unit analysis and prerequisite tests and ends with hypothesis testing using product moment and simple linear regression tests. The results of this study were 1) The level of the used of Game-Based learning (Baamboozel) in IV grade students of Madrasah Ibtidaiyah Payungan was very high, seen in the classification of its value showes 38 students were in the category of very high value category. 2) The level of students’ learning motivation of IV grade students of Madrasah Ibtidaiyah Payungan showed the highest value of 80 and the lowest value was 72, while the mean was 77,15 with a standard deviation of 2,37. It was known that the value of student learning motivation in IPAS lessons was 20 students got quite high scores. 3) on the product moment test obtained 0,758 with sig. (2 tailed) 0,00, it could be concluded that between the use of Game-Based Learning (Baamboozle) and students’ learning motivation had significant relationship